TRENDS AND PATTERNS OF RESEARCH PRODUCTIVITY OF INDIAN SCHOLARS IN INTERNATIONAL LIBRARY AND INFORMATION SCIENCE JOURNALS: A BIBLIOMETRIC PERSPECTIVE - Suma B.; B. U. Kannappanavar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the trends and patterns of research productivity of Indian scholars in international Library and Information Science (LIS) journals from 1975 to 2023 using bibliometric methods. A dataset of 6,128 publications indexed in Scopus across 71 Q1 and Q2 LIS journals was analysed to assess growth, authorship, collaboration, institutional and state-level contributions, and citation impact. The findings reveal four distinct phases of productivity: minimal and irregular growth until 1990, gradual expansion from 1991 to 2005, transitional growth between 2006 and 2015, and exponential output from 2016 onwards, with the last decade alone contributing over 64% of total publications. Relative Growth Rate (RGR) and Doubling Time (Dt) highlight significant surges in 2012 and 2016, followed by a more stable yet high-output period. State-wise analysis shows Tamil Nadu and Delhi as dominant contributors, while Uttar Pradesh and Punjab demonstrate disproportionately high citation impact. Institutionally, Anna University leads in volume, whereas IIT Delhi and Banaras Hindu University stand out for scholarly influence through high citation averages. Among authors, Vivek Kumar Singh emerges as the most influential, with the highest citation impact despite not being the most prolific. The results underscore that while Indian LIS research has achieved rapid global visibility in recent years, quality and influence remain uneven across regions and institutions. The study offers critical insights for policymakers, institutions, and scholars to strengthen India’s research visibility and align future contributions with international benchmarks.